Relación entre Área Total y Área Epitelial de vellosidades placentarias porcinas en diferentes estadíos gestacionales - Merkis, C.I. (2005)
The porcine placenta is epitheliochorial and non-invasive. The maintenance of the pregnancy is supported by villi which make interdigitations between the epithelial trophoblastic cells and the epithelial uterine cells during pregnancy. The objective of this work was to study the placental tissue using a digital analysis of images that allows measuring the total area and the epithelial area. Histologic sections of the five porcine placenta of 28, 55, 70 days and a term were used. The measure of the morphometric parameter was realized by digital analysis of images. Results: at 55 days of pregnancy the mean values of villi total area were comparable to that of placenta at term. The total area decreased significantly at about 70 days of pregnancy. The epithelial area developed since 28 days of gestation, decreased about 70 days and increased in placenta at term. Conclusion: villi showed the largest development in porcine placent of 55 days of pregnancy, decrease of total area and epithelial at 70 days and increase of epithelial area in placent at term.